Teknologi Augmented Reality Di Era 5.0 untuk Meningkatkan Pengetahuan dan Konsentrasi Peserta Didik Tingkat SMP Pada Pembelajaran PJOK - Ariestika, Elsa; Amni, Hazrina; Sari, Nugrahani Febrina; Wulandari, Indri (Jurnal Sporta Saintika, 2023)
This study aims to increase the knowledge and concentration of junior high school students in PJOK learning with augmented reality technology. This study uses a quantitative approach method with an experimental design "the one group pretest posttest design" or there is no control group for experimental tests whether the resulting product is feasible and effective or not. The sample used was 60 students of SMPN 7 Kota Serang with purposive sampling technique. The instrument used in this study used 20 questions to measure knowledge, and measured concentration using a concentration test grid. The results showed that there was a significant increase in knowledge (49.47%) and concentration (55.15%) of junior high school students in PJOK Learning after using augmented reality technology AR) in the 5.0 era.